A longitudinal examination of collaboration diversity among communication scholars: 19902023 - Shan Xu; Kulsawasd Jitkajornwanich; Prabu David; Hye-jung Park; Yani Zhao; Jeffery Du; Thanathip Chumthong (My University, 2024)
Abstract This study examines racial diversity in co-authorship in articles published in communication journals and its association with citations accrued over time. We analyzed 76,217 publications from 73 communication journals, spanning from 1990 to 2023, with a focus on racial diversity in authorship as an indicator of collaboration diversity. Our results reveal that diversity is positively associated with the number of citations received, with this positive effect increasing over time. In addition, non-White lead authors collaborated more diversely, whereas White authors exhibited a faster increase in collaboration diversity over the years. Furthermore, the positive association between collaboration diversity and citations was more pronounced when the lead author was non-White than when White. Additional analyses show a concerning disparity: While non-White first authors are equally likely as their White counterparts to publish in top journals, they receive significantly fewer citations.
Keywords: Gender Diversity and Inequality